Molybdenum and tungsten manufactured by selective laser melting: Analysis of defect structure and solidification mechanisms. (November 2019) - Braun, J.; Kaserer, L.; Stajkovic, J.; Leitz, K.-H.; Tabernig, B.; Singer, P.; Leibenguth, P.; Gspan, C.; Kestler, H.; Leichtfried, G.
Abstract: In this work, processing of molybdenum and tungsten by Selective Laser Melting (SLM) is analyzed. The study reveals the impact of the oxygen content of the powder, the process atmosphere and the temperature of the substrate plate on the structural and mechanical properties of the processed material. For clarifying the causes and mechanisms for the formation of defects in molybdenum and tungsten processed by SLM, the samples were examined by x-ray, scanning and transmission electron microscopy including elemental distribution maps and crystallographic analyses by electron backscatter diffraction. Impurities, mainly oxygen, were identified as cause for the predominant defect structure comprising cracks and residual porosity. During processing, oxygen in the form of molybdenum/tungsten oxide, segregates at the grain boundaries, thereby inducing hot cracking. This is due to the lower melting point of the eutectic compared to the matrix phase. Moreover, the oxygen impurities were found to weaken the grain boundaries and thus increasing the risk for cold cracking and leading to a higher Ductile-to-Brittle Transition Temperature (DBTT). Subsequently, the combination of cracks through hot cracking at planar solidified grain boundaries and cold cracking along weakened grain boundaries during rapid cooling from the melting point creates the crack network generally found in molybdenum and tungsten processed by SLM. Also a substrate plate temperature of 1000 °C does not prevent the formation of cracks in tungsten caused by oxygen segregations. Graphical abstract: Unlabelled Image Highlights: Oxygen is responsible for defects in additively manufactured molybdenum and tungsten. High oxygen content is introduced by oxidized powder surface and residual oxygen in building chamber. Hot cracking and embrittled grain boundaries are caused by segregated oxygen. Molybdenum/tungsten oxides were found at intergranular fracture surfaces. Heating of the substrate plate to 1000 °C does not avoid cracking in tungsten.